Verso casa: lo spazio domestico nei romanzi multigenerazionali dell’Ottocento e del Duemila in Italia (apropos [Perspektiven auf die Romania], 2025)
The house constitutes a central topos of the multigenerational novel as we’ve have known it since the late 19th century. In I Malavoglia (1881) by Giovanni Verga and I Viceré (1894) by Federico de Roberto, for instance, the family house is not only reduced to a physical space where characters act and socialize, but is also a metaphor for the lineage itself and its destiny. This spatial paradigm has changed considerably in the multigenerational novels of the 2000s in Italy, such as Fra due mari (2002) by Carmine Abate, Conta le stelle, se puoi (2008) by Elena Loewenthal, and Canale Mussolini (2010) by Antonio Pennacchi. In these novels, the unity of the home, understood as the original place of ancestry, has been replaced by its remoteness in space and time: this is symptomatic of the individual’s internal fragmentation, but also of their search for their own identity and their own space in the family genealogy and in history.
Keywords: family house; multigenerational novel; genealogy; memory; return